Reliability-Centered Process Control in Wastewater Treatment: Quantifying Effluent Compliance Risk Under Sensor Drift, Process Upsets, and Control-Loop Uncertainty - Khamla Phommavong Khamla Phommavong (Kalam Practica Media, 2025)
This article presents a reliability-centered process control framework that treats wastewater treatment as an end-to-end decision system in which sensor uncertainty, model mismatch, and actuator constraints propagate into effluent quality risk. A quantitative scenario-based study is developed for a conventional activated sludge process with nitrification and denitrification, comparing four operational architectures that span baseline PID control, feedforward-enhanced aeration, hybrid risk-based control with supervisory logic, and governance-optimized operation with drift-aware sensing, quantile-based alarm thresholds, and two-tier intervention pathways. The analysis uses engineering metrics that translate to plant management and compliance planning, including probability of exceeding effluent limits for biochemical oxygen demand and ammonia, expected duration and severity of violations, time-to-detection of process upsets, and cost–risk trade-offs that incorporate energy usage and chemical dosing. Results indicate that (i) compliance risk is dominated by tail events driven by combined hydraulic shocks and influent ammonia spikes rather than by steady-state control quality, (ii) sensor drift in dissolved oxygen and ammonia probes can create false stability that delays corrective action and increases violation duration even when average readings appear acceptable, and (iii) reliability improvements are achieved more consistently through governance of sensing and alarms and through structured escalation logic than through controller sophistication alone. The paper provides copy-ready tables and publication-ready figure prompts to support Techne submission and practical implementation.